2015
DOI: 10.1063/1.4938749
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation at the contact line triggered by transient electrowetting fields

Abstract: Supercooled water is found to have a significantly enhanced freezing temperature during transient electrowetting with electric fields of order 1 V/lm. High speed imaging reveals that the nucleation occurs randomly at the three-phase contact line (droplet perimeter) and can occur at multiple points during one freezing event. Possible nucleation mechanisms are explored by testing various substrate geometries and materials. Results demonstrate that electric field alone has no detectable effect on ice nucleation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…optical observations of immersion mode nucleation on substrates. As previously demonstrated (Yang et al 2015;Gurganus, Kostinski, and Shaw 2011;Yang et al 2018;Holden et al 2019), higher frame rates than used here are imperative when the sample is immersed in water because the ice can spread to millimetre length-scales on the order of milliseconds after the nucleation event.…”
Section: Discussion and Outlookmentioning
confidence: 79%
“…optical observations of immersion mode nucleation on substrates. As previously demonstrated (Yang et al 2015;Gurganus, Kostinski, and Shaw 2011;Yang et al 2018;Holden et al 2019), higher frame rates than used here are imperative when the sample is immersed in water because the ice can spread to millimetre length-scales on the order of milliseconds after the nucleation event.…”
Section: Discussion and Outlookmentioning
confidence: 79%
“…More recently, some studies demonstrated the increase of freezing temperature with external applied field whereas others claimed the opposite . But one important conclusion is that the results are strongly impacted by experimental procedure . Fundamental interfacial mechanisms underlying electrofreezing are reviewed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al . measured the freezing fraction of drops deposited on glass covering a Si substrate as a function of temperature and applied voltage.…”
Section: Resultsmentioning
confidence: 99%
“…These correlations may be due to storm invigoration (Rosenfeld et al, 2008;Tinsley, 2012;Tinsley & Yu, 2004). For contact ice nucleation, the work of Yang et al (2015) adds to that of Abbas and Latham (1969) discussed by Tinsley and Dean (1991), suggesting that liquid shear in the strong electric fields between the charged particle and its image, at the moment of contact of a charged INP with a supercooled droplet, may further increase the efficiency and thus the amount of contact ice nucleation.…”
Section: Atmospheric Relevancementioning
confidence: 96%